Potential Map for the Installation of Concentrated Solar Power Towers in Chile - Catalina Hernández; Rodrigo Barraza; Alejandro Saez; Mercedes Ibarra; Danilo Estay (Energies, 2020)
This study aims to build a potential map for the installation of a central receiver concentrated solar power plant in Chile under the terms of the average net present cost of electricity generation during its lifetime. This is also called the levelized cost of electricity, which is a function of electricity production, capital costs, operational costs and financial parameters. The electricity production, capital and operational costs were defined as a function of the location through the Chilean territory. Solar resources and atmospheric conditions for each site were determined. A 130 MWe concentrated solar power plant was modeled to estimate annual electricity production for each site. The capital and operational costs were identified as a function of location. The electricity supplied by the power plant was tested, quantifying the potential of the solar resources, as well as technical and economic variables. The results reveal areas with great potential for the development of large-scale central receiver concentrated solar power plants, therefore accomplishing a low levelized cost of energy. The best zone is located among the Arica and Parinacota region and the northern part of the Coquimbo region, which shows an average cost of 89 USD/MWh, with a minimum of 76 USD/MWh near Copiapó.